Application of herbicides on parental lines (A clearfield® and R) of hybrid rice at post-flowering stage for production. - MONDO, V. H. V. (2019)
The hypothesis of this study is based on the fact that parental line A-Clearfield® (male-sterile genotype) (Clearfield provide has tolerance to imidazolinone herbicides) and line R (male-fertile genotype - pollinator) is sensitive to the herbicide. So after flowering, we may apply an imidazolinone herbicide (Kifix®) to the plantings to kill line R, and harvesting only the hybrid seeds. The objective was to test the use of imidazolinone herbicide on parental lines (A-Clearfield® which is resistant to Kifix herbicide) and R no Clearfield® (non-resistant to Kifix genotype) as a strategy to improve production of hybrid seed in rice. Two trials were conducted to evaluate (A) the use of doses of imidazolinone herbicide in line R (plant control, number of grains per panicles, grain yield and seed germination; and (B) the use of different doses of imidazolinone herbicide in line A Clearfield® grain yield and seed germination. Trials were conducted in the tropical region of Brazil in randomized complete block design in factorial scheme 5 x 2 x 2. The treatments were the combination of five Kifix (Imazapyr, 525 g kg-1 + Imazapic, 175 g kg-1) rates applied on two no Clearfield® rice genotypes (first trial) or Clearfield® rice genotypes (second trial) in two growing seasons. The results showed application of herbicide doses higher than 150 g ha-1 after full flowering stage can cause reduction in growth and development of no Clearfield® rice. The use of Kifix herbicide in CL (Clearfield®) rice cultivars did not affect the grain yield, mass of 1000 grains, seed germination, first count germination, seedling emergence and seedling length. New researches should be done to define plant arrangement suitable for line R (no Clearfield®) and line A Clearfield® to find the optimum condition to produce hybrid seeds. From our results, we could see that the use of parental line A Clearfield® with a line R no Clearfield®, after flowering, provided the production of only hybrid seeds in the area, without reduction in seed quality.